Network Pharmacology-Based Analysis of Pogostemon cablin (Blanco) Benth Beneficial Effects to Alleviate Nonalcoholic Fatty Liver Disease in Mice - Yizhe Cui (Frontiers Media S.A., 2021)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and is associated with high morbidity and mortality. Pogostemon cablin (Blanco) Benth/Huo Xiang (HX) is a perennial herb with unique anti-oxidant and anti-inflammatory properties, and thus, can positively affect liver function. In this study, we used network pharmacology to predict the potential mechanism of HX on NAFLD. Pharmacological experiments were used to verify the effect of HX on the functions of NAFLD. Network pharmacology identified nine components that interacted with 82 NAFLD-related targets, revealing four target genes: TNF, IL6, TP53, and AKT1. HX prevents the development and progression of NAFLD through different pathways and targets with quercetin-regulated lipid metabolism, anti-inflammatory, and anti-oxidant pathways playing an essential role in the treatment of NAFLD. Compared with feeding HFD, HX significantly attenuated lipid accumulation in vivo with mice and also in vitro with mouse liver cells. A high dose of HX decreased hepatocyte lipid accumulation and the abundance of SREBF1 and FASN. Validation experiments revealed that HX inhibited the activation of NF-κB/IκB signaling and decreased the release and levels of pro-inflammatory factors (TNF-α and IL-6). These data suggest that HX can attenuate abnormal lipid metabolic responses and enhance antioxidant mechanisms. Thus, the pharmacological effects from plants used in traditional Chinese medicine are achievde through a multi-level response.